Mortalidade de pacientes idosos com fratura de quadril tratados cirurgicamente em um hospital da região amazônica durante a pandemia por Sars-cov-2 - PORFÍRIO, Danillo Monteiro (2023)
In 2020, due the pandemic caused by SARSCoV2, isolation measures were established to interrupt the virus transmission chain. Even in isolation, elderly patients were still exposed to the risks of falling. Hip fracture caused by falls is a serious condition that poses a high risk of mortality for older people. Thus, the study proposes to evaluate the mortality rate up to one year of elderly patients undergoing hip fracture surgery during the COVID19 pandemic in an orthopedic trauma service. An analytical retrospective cohort study was carried out, using data from patients’ medical records aged 60 years or older, who sustained fractures in the proximal third of the femur (neck, intertrochanteric or subtrochanteric) from March/2020 to February/2021. Data from 356 patients were considered, with 68.53% female patients and a mean total age of 78.75 ± 9 years. The mortality rate was 10.95%, with most deaths occurring within 180 days and most causes due to acute respiratory failure (2.8%). Men had 2.57 times greater risk of death up to 365 days, in addition to a 5.87 times greater risk for patients aged 90 years or older. Patients with COVID19 infection history had a 5fold increased risk of death in one year. Patients with Parkinson's disease and pulmonary comorbidities had elevated risks without statistical significance. There was a significant difference between the days of hospitalization of patients who died and patients who survived the first 30 days (p=0.044). Patients operated within 48 hours from fracture did not present any death (p<0.0001). Thus, the care of hip fractures, even in a pandemic period, must present a flow that guarantees the safety and health of elderly patients.